Pencarian Jalur Alternatif berbasis Algoritme Yen's pada Jaringan Software Defined Network - Dyan Krisyanto; Reza Andria Siregar; Kasyful Amron (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2022)
Software-Defined Networking or SDN is an architecture on a network that has manageable and adaptable properties, this will provide advantages when implementing it. Various examples of network applications that can be applied to SDN, for example is routing. With regard to routing, the routing path will be more efficient when the routing path that has been built can vary according to the actual situation on a network. So that if a problem arises such as a path failure on the active path or the path is not in accordance with the standard, then the path will always use the existing alternative path. The reactive nature of routing will make it easier for network administrators to monitor the network. In its application, routing needs an algorithm to find a path. In this research, Yen's algorithm is used to find alternative paths. The test is conducted to find out how the performance of alternative path search and the performance of Yen's algorithm is. The test results show that the response time test for searching paths under normal conditions gets an average of 6.245 seconds while for alternative route searches it gets an average of 50,825 seconds. Furthermore, for testing the recovery time gets an average of 159.68 seconds. Then the packet loss test obtained a value of 58.2%. The convergence time test does not show a significant difference based on the average results obtained on the normal path, which is 0.030 seconds and the average on the alternative path is 0.036 seconds.